Microbial Assessment of Drinking Water Sources in Himachal Pradesh, India - Sidharath Dev Thakur; Ashok Kumar Panda; Vaneet Diwan; Pravesh Kumar; Madhumeet Singh; Dinesh Kumar Sharma (Indian Journal of Public Health)
World Health Organization and Bureau of Indian Standards recommend zero tolerance for coliforms in drinking water. A total of 592 drinking sources from 11 districts of Himachal Pradesh, India, were screened for coliform contamination and the presence of fecal origin Escherichia coli. The study revealed contamination levels of 55.6% and 9.6% for coliforms and fecal E. coli, respectively. The coliform contamination levels were significantly higher for natural water sources (67.1%) and public water supplies (59.7%) compared to groundwater sources (31.5%). The presence of fecal-origin E. coli was highest (11.6%) in public supplies, followed by natural (9.9%) and groundwater (4.7%) sources.